Incorporating weight management and physical activity throughout the cancer care continuum : proceedings of a workshop - Balogh, Erin (Online access: NCBI NCBI Bookshelf., 2018)
"The National Cancer Policy Forum of the National Academies of Sciences, Engineering, and Medicine held a public workshop, Incorporating Weight Management and Physical Activity Throughout the Cancer Care Continuum, on February 13 and 14, 2017, in Washington, DC. The purpose of this workshop was to highlight the current evidence base, gaps in knowledge, and research needs on the associations among obesity, physical activity, weight management, and health outcomes for cancer survivors, as well as to examine the effectiveness of interventions for promoting physical activity and weight management among people living with or beyond cancer. Workshop sessions also reviewed the opportunities and challenges for providing weight management and physical activity interventions to cancer survivors. This publication summarizes the presentations and discussions from the workshop"--Publisher's description.